Overnutrition as a Risk Factor for More Serious Respiratory Viral Infections in Children: A Retrospective Study in Hospitalized Patients; [el Exceso de Peso Como Factor de Riesgo Para Infecciones Virales Respiratorias Más Graves en Menores de Edad: Estudio Retrospectivo en Pacientes Hospitalizados] - Zorondo-Rodriguez, F (Sociedad Espanola de Endocrinologia y Nutricion, 2023)
Background: The prevalence of obesity has increased dramatically in children worldwide. Obesity has been recognized as a risk factor for more serious viral respiratory infections, mainly in adults. Objective: To study the relationship between overnutrition (obesity and overweight) and clinical severity in children hospitalized with acute respiratory infections of viral origin. Methods: One hundred and forty-three clinical records of children between 2 and 18 years old hospitalized for acute respiratory infection at Clínica Dávila (2014-2018) were analyzed, recording the respiratory viruses detected at the time of hospitalization, weight, and height. Nutritional status was estimated using Z score or body mass index, according to age. Results: Eighty-tree3 children (58%) were positive for more than one respiratory virus. The main virus detected in monoinfection was adenovirus (9.8%), followed by respiratory syncytial virus (7.7%) and parainfluenza virus (7.7%). There were no deaths. Patients with obesity presented more days of hospitalization (P = .04), oxygen therapy (P = .03) and mechanical ventilation (P < .001), as well as a higher probability of requiring mechanical ventilation (P = .001) and of ICU admission (P = .003) compared with children with normal weight. Patients with overweight presented more days of mechanical ventilation (P < .001) than patients with normal weight. No significant differences were found between the presence of viral coinfection and nutritional status. Conclusion: Overnutrition is associated with greater severity of viral respiratory infection in hospitalized children. © 2023 SEEN y SED